2019
DOI: 10.1177/1362168819877080
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ discourse on English for young learners

Abstract: English, the global lingua franca, enjoys a growing status worldwide. The high status of English is also linked to the increasing interest in teaching English to young learners (EYL), and is reciprocally linked to complex political, cultural and social forces. Research on the advantages of learning English at a young age is controversial and inconclusive, but despite uncertainties it seems that EYL will continue to be a growing trend. This study aimed to understand the forces that drive the EYL phenomenon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…By addressing the first research question of motives, the study reveals that, as indicated by all the participants, the hope of optimising children's future success through English learning can be a reason driving parents to pay the tuition fee. This finding exemplifies a typical context with 'English fever' (Chik and Besser 2011;Fish, Parris, and Troilo 2017;Park 2009) where parents believe in the instrumental values of English for their children's academic, social and economic advancement (Carmel 2019;Wei 2011). Another motive concerning 'outsourcing' English learning to EPT reflects parents' perceived incompetence in teaching their own children and the possible limitations of schooling.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…By addressing the first research question of motives, the study reveals that, as indicated by all the participants, the hope of optimising children's future success through English learning can be a reason driving parents to pay the tuition fee. This finding exemplifies a typical context with 'English fever' (Chik and Besser 2011;Fish, Parris, and Troilo 2017;Park 2009) where parents believe in the instrumental values of English for their children's academic, social and economic advancement (Carmel 2019;Wei 2011). Another motive concerning 'outsourcing' English learning to EPT reflects parents' perceived incompetence in teaching their own children and the possible limitations of schooling.…”
Section: Discussionmentioning
confidence: 59%
“…To date, there is a paucity of empirical data showing parents' motives for paying for their children's EPT within this privatised educational context. This is an important area of research since parents are key stakeholders of EPT as consumers of this monetarily purchasable resource for their children (Carmel 2019;Gupta 2020). The increasingly prevailing ideology of parentocracy, fuelled by 'English fever' (Fish, Parris, and Troilo 2017;Park 2009) in non-English-speaking societies worldwide, has also suggested an urgent need to understand the EPT phenomenon from the parental perspective.…”
Section: Introductionmentioning
confidence: 99%
“…For many parents, English is regarded "as a valuable asset associated with prestige and economic welfare", which can determine someone's opportunities of success and social mobility (Carmel, 2019, p. 1). Consequently, many parents believe that the earlier they start learning, the better their chances to succeed (Carmel, 2019;Nikolov, 2016) despite strong evidence which proves otherwise (e.g., Rokita-Jaśkow & Ellis, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…what subjects are important, and which are not) also play key roles in the legitimation of commodification. In this context, learning English has become instrumental to the narrative of (global) success, and it plays a determining role in an individual's social dimension (Carmel, 2019;Nikolov, 2016). In South America, English remains the quintessential foreign language to teach at schools, largely supported by a neoliberal narrative of potential opportunities (Kamhi-Stein et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation